A Portrait of Civics Learning Strategies Oriented to National Character at SMA Negeri 1 Kabila - Nggilu, Ariyanto; Adhani, Yuli; Nadia, Sabrina; Dotutinggi, Sanri J. (Journal of English Language and Education, 2026)
This study aims to photograph the learning strategy of PPKn oriented to national character in SMA Negeri 1 Kabila. The research uses a descriptive qualitative approach with a case study design through in-depth interviews, learning observations, and documentation studies. The results of the study show two main findings. First, the PPKn learning strategy applied is semi-participatory, characterized by the use of discussions and questions and answers that are still dominated by the pedagogical control of teachers. Second, the implementation of learning strategies is supported by teacher commitment and a conducive school climate, but is limited by time constraints, passive student learning culture, and lack of experiential learning. This research emphasizes the need to transform PPKn learning strategies that are more dialogical and contextual to strengthen students' national character in a sustainable manner.